Factors associated with pain coping and catastrophising in patients with systemic lupus erythematosus: a cross-sectional study of the LuLa-cohort. Issue 1 (12th November 2015) - Fischin, Julia; Chehab, Gamal; Richter, Jutta G; Fischer-Betz, Rebecca; Winkler-Rohlfing, Borgi; Willers, Reinhart; Schneider, Matthias
Abstract : Objective: The aim of this study was to identify factors associated with pain coping and catastrophising in patients with systemic lupus erythematosus. Methods: All patients were participants of the lupus erythematosus long-term study, which is based on patient-reported data assessed among members of the German Lupus Erythematosus Self-Help Organization. Assessments were performed by means of a questionnaire. Among self-reported clinical data the Pain-Related Self Statements Scale (PRSS) was included. To depict significant differences univariable analyses were carried out using non-parametrical rank tests. To examine factors influencing our outcome variables, we performed a multivariable stepwise regression model including variables that presented significantly in the univariable analysis. Results: 447 cases (94.9% female) were analysed showing a mean catastrophising score of 1.1 (SD 0.8) and a mean coping score of 2.8 (SD 0.9) in the PRSS subscales. Higher catastrophising quartiles went along with higher experienced pain, lupus activity, fatigue, damage and decreased health related quality of life, whereas they presented inversely for coping. In our multivariable model, factors associated with catastrophising were: number of lupus-specific drugs (p value 0.004), pain in the last 7 days (p value 0.034), the Short Form 12 Health Survey Mental Component Summary (p value <0.001) and disease activity measured by the Systemic Lupus Activity Questionnaire (p value 0.042). Social participation reflected by performed leisure activities such as dancing or bowling had a positive association with coping (p value 0.006). In contrast, other health related physical activities and their extent had no impact on coping. A direct association between the amount of pain coping and catastrophising, as well as a great impact of the catastrophising, respectively, coping level on physical and mental functioning could be shown. Conclusions: Reduction or increase of detected factors might lead to a modification of pain coping and catastrophising and offer an approach to more effective care in patients with SLE.